2016
DOI: 10.1021/acsami.5b10667
|View full text |Cite
|
Sign up to set email alerts
|

Solid–Liquid Self-Adaptive Polymeric Composite

Abstract: A solid-liquid self-adaptive composite (SAC) is synthesized using a simple mixing-evaporation protocol, with poly(dimethylsiloxane) (PDMS) and poly(vinylidene fluoride) (PVDF) as active constituents. SAC exists as a porous solid containing a near equivalent distribution of the solid (PVDF)-liquid (PDMS) phases, with the liquid encapsulated and stabilized within a continuous solid network percolating throughout the structure. The pores, liquid, and solid phases form a complex hierarchical structure, which offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Synthesis of Spherical Composite : To synthesize the polymer encapsulated liquid shells, the authors followed a similar procedure to the one reported by Dong et al The authors took PVDF (Alfa Aesar, 23 500–29 500 P) and dissolved into tetrahydrofuran (THF) while under magnetic stirring. The solution was monitored until it reached homogenization (≈3 h).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Synthesis of Spherical Composite : To synthesize the polymer encapsulated liquid shells, the authors followed a similar procedure to the one reported by Dong et al The authors took PVDF (Alfa Aesar, 23 500–29 500 P) and dissolved into tetrahydrofuran (THF) while under magnetic stirring. The solution was monitored until it reached homogenization (≈3 h).…”
Section: Methodsmentioning
confidence: 99%
“…The material was cycled constantly at 5 Hz and a difference in the stiffness behavior is clear. As more spheres are added the material begins to exhibit increased stiffening, or self‐stiffening as described by others . Self‐stiffening has generally been seen when performing isothermal tests with a multitude of cycles over time.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Consequently, scientific and technical studies of PDC with liquid droplets are new and have seldom been reported. 27,28 In sections 2 and 3, we will demonstrate weak droplets as a flexible, powerful, and kinetics-favored second phase for design of PDCs with unusual and novel mechanical properties.…”
Section: Introductionmentioning
confidence: 99%